Analisis Opini Publik Terhadak Konflik Palestina dan Israel - Yogi Pratama; Arfian Suryasuciramdhan; Indra Bahari Saputra; Deva Satria Pamungkas (STIKes Ibnu Sina Ajibarang, 2024)
This journal was created to find out various views from community groups regarding the conflict between Palestine and Israel. Palestine is a country located in the Middle East at the same time as Israel. This conflict will take the point of view of the parties that took part in the protests regarding these two countries. Many speculate or argue that this conflict occurred because of religion. On the other hand, there are those who consider this incident to be the result of political interference, but in reality now this conflict has been around for a long time and has Now there is still no agreement for peace.